A Correlative Study to Assess the Relationship among Ameloglyphics, Cheiloscopy, Rugoscopy in Skeletal and Dental Malocclusions - Akkina, Tanmayi; Ponnada, Swaroopa; Gandikota, Chandrasekhar; Gandikota, Akshara (Orthodontic Journal of Nepal, 2023)
Introduction: Benefits of preventive and interceptive orthodontic procedures can be availed by early prediction of malocclusion. Early diagnosis is achievable when parameters having similar embryological origin and development period, similar to that of the craniofacial structures are identified and studied. Few such parameters are the enamel rod end patterns, lip prints, and palatal rugae patterns. The intent of this study was to assess the correlation between ameloglyphics, cheiloscopy, rugoscopy and skeletal and dental malocclusions. Materials and Method: A cross-sectional study with one hundred subjects were classified into 3 groups based on cephalometric analysis into skeletal class I, class II and class III malocclusion and were further divided into 4 dental malocclusion groups namely class I, class II division 1, class II division 2 and class III based on the Angle's classification of malocclusion. Ameloglyphics patterns, lip prints and palatal rugae patterns were recorded for each subject and statistically analyzed with chi-square test and Spearman correlation test. Result: Class I malocclusion subjects revealed a predominant curve palatal rugae pattern, type II lip print pattern and wavybranched ameloglyphics patterns were observed with statistically significant association. In class II malocclusion, the predominant palatal rugae pattern observed was straight pattern, type I lip print pattern and linear branched ameloglyphics patterns were statistically significant. Subjects in class III malocclusion group were associated significantly with the annular pattern of palatal rugae, type I lip print pattern, and stem pattern of ameloglyphics. Conclusion: A curve rugae pattern in class I malocclusion, a straight pattern in class II malocclusion, and an annular pattern in class III malocclusion were observed. For the Lip Prints, a highly statistically significant association was observed between class I malocclusion and type II lip print pattern. Ameloglyphics, revealed a statistically significant association between wavy branched pattern and class I malocclusion, linear branched pattern and class II malocclusion and stem pattern with class III malocclusion.